THE USE OF HYBRID/BLENDED LEARNING IN UNDERSTANDING OF ENGLISH STRUCTURE SUBJECT TO IMPROVE STUDENTS' ACHIEVEMENT AND THEIR DIGITAL LITERACY - Lungguh Halira Vonti; Mursidah Rahmah (UNIVERSITAS PAKUAN, 2019)
This research is aimed to find out whether the aplication of blended learning has significant effect on the students' achievement of Understanding English Structure subject or not, and to know if the students' achievement after the application of blended learning is better than the prior knowledge of the subject. It was also to see if the application of blended learning give positive effect to the students' digital literacy. Hence, the researcher employs experimental research by giving hybrid-learning model as the treatment. It is expected that the students can achieved good score about English structure. The research involves the second semester students of English Language Education Study Program of FKIP Pakuan University. They were chosen through purposive sampling technique. Based on the result of data analysis by using ANOVA, the students' achievement in strcture class was improved. Based on the t-test results it is known that the average pre-test is 63.4 and after treatment in the form of learning using a hybrid / blended learning model, the average post-test value becomes 86 so that the increase is 22.6. So that it can be stated there is a significant increase in student learning outcome scores by using hybrid / blended learning models. The positive result was also gained from the digital literacy questionnaire. Most of the students' digital literacy was improved significantly at about 10 to 20%. Therefore, it can be stated that hybrid-learning model can improve students' achievement in grammar class and also can improve their digital literacy.